2015
DOI: 10.1155/2015/370314
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Subgingival Periodontal Pathogens and Association with the Severity of Periodontitis in Patients with Chronic Kidney Diseases: A Cross-Sectional Study

Abstract: Background. The aim of our study was to assess the subgingival profile of 9 periodontal pathogens, by means of real-time PCR, in a group of predialysis chronic kidney disease patients with and without periodontal disease and to identify the risk factors associated with periodontal disease in these patients. Material and Methods. This is a single centre cross-sectional cohort study performed on 70 CKD patients. Patients received a full-mouth periodontal examination and the following parameters were assessed: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
0
23
0
2
Order By: Relevance
“…A total of 2,763 studies were identified from Medline and Scopus, and 1,934 studies remained after removing duplicates. Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2,763 studies were identified from Medline and Scopus, and 1,934 studies remained after removing duplicates. Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors. Of the remaining 50 studies, 45 objectively assessed OH using an oral examination.…”
Section: Resultsmentioning
confidence: 99%
“…Table describes the characteristics of 7 case‐control studies and 38 cross‐sectional studies on the non‐directional association, and lists them in reverse publication order . Among them, 24 had a statistical analysis, but 7 did not consider any confounding factors (Appendix A) .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the various demographic characteristics of the recruited subjects in each study may have an impact on the results of this systematic review (Table ). First, the age range and number of remaining teeth of the participants vary widely. The lower number of teeth may reflect poorer periodontal status in some degree.…”
Section: Discussionmentioning
confidence: 99%
“…If in the healthy individuals, the oral biofilms are comprised mainly of gram-positive facultative anaerobes (Streptococcus anginosus and A. naeslundii), in the above mentioned pathologic conditions, the percentage of gram-negative anaerobic bacteria increases and may include Aggregatibacter (previously Actinobacillus) actinomycetemcomitans, Porphyromonas gingivalis, P. intermedia, Bacteroides forsythus, Campylobacter rectus, Eikenella sp., Peptostreptococcus micros, Streptococcus intermedius, Prevotella sp., Fusobacterium sp., Capnocytophaga sp., Veillonella sp., Treponema and other on-cultivable spirochetes, and the bacterial counts associated with the disease are up to 10(5) times larger than those of the same species found in healthy individuals [6,7].…”
Section: Introductionmentioning
confidence: 86%